Three weeks of intermittent hypoxic training affect antioxidant enzyme activity and increases lipid peroxidation in cyclists - Michalczyk, M. M.; Chycki, J.; Zajac, A.; Petr.M.; Czuba, M.; Langfort, J. (Monatshefte für Chemie - Chemical Monthly, 2019)
The aim of the present study was to evaluate the influence of intermittent hypoxic training (IHT) on antioxidant status in elite cyclists. Fifteen male, elite cyclists were randomly divided into the IHT group (IHT-G) and a normoxia control group (CG). The subjects in IHT-G exercised under normobaric hypoxia environment (O2?=?15.2%) at intensity of 95% of the lactate threshold (LT) for 3 weeks, whereas the CG exercised under normoxia with intensity of 100% LT. The following variables were measured: superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), reduced glutathione (GSH), uric acid (UA), total antioxidant status (TAS), malondialdehyde (MDA), and creatine kinase (CK). All variables were evaluated at baseline and post-exercise, both at rest and following the progressive exercise test (PT). After 3 weeks of training, significant intragroup differences occurred in MDA, GSH, and TAS values, and in GPX and CK activity. There were also significant changes in IHT-G before the experiment and after the PT in SOD, GPX, and CK activity, and in levels of TAS and MDA. After the 3 weeks of training, and following the PT, there were significant differences in SOD, CAT, GPX, and CK activity as well as in levels of UA and MDA. In the CG, before and after the intervention, and the PT, SOD, CAT, and CK activity as well as UA, TAS, and MDA concentrations were significantly different from resting condition. IHT significantly affects SOD, CAT, and MDA in competitive cyclists. We observed lower antioxidant enzyme activity and higher MDA concentration in the IHT-G compared to the CG. This confirms that exercise under hypoxia generates higher oxidative stress than the same training loads performed under normoxia conditions.